Economic policy uncertainty and grain futures price volatility: evidence from China. Issue 4 (25th October 2019) - Xiao, Xiaoyong; Tian, Qingsong; Hou, Shuxia; Li, Chongguang
Abstract : Purpose: The purpose of this paper is to investigate the influence of economic policy uncertainty (EPU) on China's grain futures prices. Related literature has discussed several factors contributing to the dramatic boom and bust in China's grain futures prices, but has overlooked the influence of EPU. Design/methodology/approach: The study employs a newly developed time-varying parameter vector autoregressive model to study and contrast the impact of different types of uncertainty on China's grain futures prices. The directional volatility spillover index is used to measure the impact of EPU on China's grain futures prices and compare the differences among commodities. Findings: The results show that EPU affects China's grain futures prices significantly. The 2008 global financial crisis had stronger influence on China's grain futures prices than other types of uncertainty. Furthermore, EPU has smaller influence on wheat futures price than on maize and soybean. The Chinese Government interventions may be the reason for this difference. Originality/value: This study addresses the lack of empirical investigation on the influence of EPU on China's grain futures price volatility.